O centro e as bordas do turismo em Foz do Iguaçu: análise das articulações dos atores locais na construção das políticas públicas de turismo municipais (1968-2019) - Welter, Viviane da Silva (2021)
The consideration of tourism as an inducer of economic development for tourist locations is unquestionable. This has been one of the justifications most frequently used by scholars and entrepreneurs or even found in government plans to justify its relevance or public investments in infrastructure. However, in addition to the economic benefits, the concept of Tourism itself has surpassed this reductionist conception, considering it as a complex phenomenon that involves, economic, environmental, social and cultural spheres. From this expansion of concept, it is questioned how the articulations of local actors have occurred in the development of municipal public policies, whether or not there was a process established between the 'centre' and the borders of tourism in Foz do Iguaçu. It was also investigated if all local actors were involved and if their local knowledge and practices were included or excluded from the planning of tourism development in Foz do Iguaçu from 1968 to 2019. In order to achieve the general objective of this thesis, in methodological terms, the evidential method (GINZBURG, 1989) was used, which seeks to observe clues, minutiae - the most negligible details. As a method of analysis, document analysis was used using public documents related to tourism planning (printed and online), as well as newspapers and photographs. Document analysis was based on Cellard (2008) and bibliographic research was used to support the analysis and interpretation of the collected data. It was confirmed the thesis that the centers and borders of tourism are well demarcated in Foz do Iguaçu, with the 'centre' being composed of the tourist trade and the Foz do Iguaçu Tourism Secretariat as articulators of the municipal tourist development; and the borders are composed by the local community directly involved, indirectly or not involved with tourism, the first two being considered supporting actors that must to be touristic awareness in order to serve the tourists. Local knowledge and practices were considered only as proposals in some documents, without further details, nor was it identified if they were executed or received support for their execution, with the predominance of investment in public infrastructure works. The path presented to change this context is cultural tourism, planned to involve the community, articulated with other policies, such as urban and cultural policies, which could provide spaces for intercultural exchanges between tourists and the host population, promoting richer cultural experiences for both.